Spirituality and Health: A Middle Eastern Perspective - Weathers, Elizabeth (Religions, 2018)
Previous spirituality studies have mostly been conducted in a Western context (Moberg 2002; Koenig et al. 2012). However, an increasing number of studies are originating from Middle Eastern countries (Koenig et al. 2012). There is a need to review the current status of Middle Eastern research to identify priorities for future research. A search was conducted in two electronic databases: CINAHL and Medline. A final sample of 28 articles was included in the review. Eighteen articles reported on quantitative studies and ten reported on qualitative studies. The majority of previous research has been conducted in Iran (n = 16) and Jordan (n = 6). A total of 3096 participants were included in the studies ranging from 2004 to 2017. Two studies were randomised controlled trials. Most of the qualitative studies aimed to gain a deeper understanding of the concept of spirituality from a Muslim-Arabic perspective. Qualitative findings have conceptualised spirituality as meaning in life, connection, peace and transcendence. In conclusion, there are both differences and similarities between Middle Eastern and Western research on spiritualty and health. Further exploration is warranted to include comparative studies between patient and nurse populations in Western societies and in the Middle East.